Chronic Headache Education and Self-management Study (CHESS) – a mixed method feasibility study to inform the design of a randomised controlled trial - Kimberley White; Rachel Potter; Shilpa Patel; Vivien P. Nichols; Kirstie L. Haywood; Siew Wan Hee; Dipesh Mistry; Dawn Carnes; Stephanie J. C. Taylor; Martin Underwood; Manjit S. Matharu; on behalf of the CHESS team (BMC Medical Research Methodology, 2019)
Abstract Background Self-management support programmes are effective in a range of chronic conditions however there is limited evidence for their use in the treatment of chronic headaches. The aim of this study was to test the feasibility of four key aspects of a planned, future evaluative trial of a new education and self-management intervention for people with chronic headache: 1) recruiting people with chronic headache from primary care; 2) a telephone interview for the classification of chronic headaches; 3) the education and self-management intervention itself; and 4) the most appropriate patient reported outcomes (PROMS). Methods Participants were identified and recruited from general practices in the West Midlands of the UK. We developed a nurse-led chronic headache classification interview and assessed agreement with an interview with headache specialists. We developed and tested a group based education and self-management intervention to assess training and delivery receipt using observation, facilitator, and participant feedback. We explored the acceptability and relevance of PROMs using postal questionnaires, interviews and a smartphone app. Results Fourteen practices took part in the study and participant recruitment equated to 1.0/1000 registered patients. Challenges to recruitment were identified. We did 107 paired headache classification interviews. The level of agreement between nurse and doctor interviews was very good. We piloted the intervention in four groups with 18 participants. Qualitative feedback from participants and facilitators helped refine the intervention including shortening the overall intervention and increasing the facilitator training time. Participants completed 131 baseline questionnaires, measurement data quality, reliability and validity for headache-specific and generic measures was acceptable. Conclusion This study indicated that recruiting people with chronic headache from primary care is feasible but challenging, our headache classification interview is fit for purpose, our study intervention is viable, and that our choice of outcome measures is acceptable to participants in a future randomised controlled trial (RCT). Trial registration ISRCTN, ISRCTN79708100. Registered 16th December 2015, http://www.isrctn.com/ISRCTN79708100